Precarization and Urban Growth in Metropolitan Mexico City - LIETTE GILBERT (Espacialidades. Revista de temas contemporáneos sobre lugares, política y cultura, 2016)
This essay examines precarization as a process produced by recent housing and urban growth agendas in Metropolitan Mexico. Our contribution highlights th e relations between housing policies and urban conditions to demonstrate that inequality and precarity are not unfortunate casualties of urbanization, but rather have been produced and sustained by governmental policies and programs. Based on a review of t he predominantly English language literature about housing policies and urban growth in both central and peripheral areas of Mexico City, we demonstrate how precarization is inherently built and normalized into past and present housing policy and urban gro wth agendas. The concept of urban precarization emerges as a double process combining socio -spatial precarization that results from systemic social structures and the institutionalization of insecurity through the planning system related to housing.